2015
DOI: 10.1002/ente.201402174
|View full text |Cite
|
Sign up to set email alerts
|

Roll‐to‐Roll Sputter Coating of Aluminum Cathodes for Large‐Scale Fabrication of Organic Photovoltaic Devices

Abstract: We report the demonstration of sputter‐coated aluminum contacts directly onto P3HT:PCBM organic photovoltaic devices using a R2R process without detrimentally influencing the performance of the devices. The final sputtered devices do not require any protective buffer layers to produce efficient performance. Depth profiling analysis of sputtered films using X‐ray photoelectron spectroscopy (XPS) indicated the presence of a 5–6 nm insulating oxide layer generated at the cathode interface for all sputtering targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…A research group from the University of Newcastle has demonstrated a pathway for ITO‐free fully R2R processed organic solar cells in a conventional geometry with a R2R sputtered aluminum top electrode . This shows that solution processable printing and coating methods can be combined with R2R vacuum techniques for the manufacturing of complete OPV modules …”
Section: Photovoltaicsmentioning
confidence: 99%
“…A research group from the University of Newcastle has demonstrated a pathway for ITO‐free fully R2R processed organic solar cells in a conventional geometry with a R2R sputtered aluminum top electrode . This shows that solution processable printing and coating methods can be combined with R2R vacuum techniques for the manufacturing of complete OPV modules …”
Section: Photovoltaicsmentioning
confidence: 99%
“…More complex structures, such as those used in the manufacture of highly efficient solar cells 37 , 38 , with the inclusion of mixed cations (Cs, MA and FA) and halides (I, Br), seem to be also feasible. Since sputtering is a very well-known technique for thin films deposition 39 43 , and its application on industrial scale 42 , 44 is already available in the market, this approach has potential to scale-up the perovskite solar cells production.…”
Section: Introductionmentioning
confidence: 99%
“…However, in terms of translating such technologies to large-scale fabrication, there has been substantially less work. Perhaps, most progress has been made in the arena of large-scale fabrication of printed organic photodiodes [15,33,105,116,[131][132][133][134][135][136][137][138][139][140][141][142][143][144][145][146][147][148][149] and field effect or electrochemically gated transistor devices [17,19,29,32,83,111,[150][151][152][153][154][155][156][157]. Each of these technologies provides a useful platform for the direct (transistors) or indirect (photodiode) detection of ionizing radiation using printed OSC technology, an area of research that is attracting increasing attention in recent years.…”
Section: Printed Device Fabricationmentioning
confidence: 99%